PENGARUH KEWIRAUSAHAAN KORPORASI PADA KINERJA EKSPOR PABRIK CRUMB RUBBER PT. SUMBER DJANTIN PONTIANAK - Dewantara, Iswan (Universitas Tanjungpura, 2012)
Corporate entrepreneurship is one of the main important factors that can determine the progress or decline of a company. The purpose of this study the authors do is to know about the Effect Analysis Corporate Entrepreneurship (Innovation, Proactive, and Risk) of the Export Performance Company in crumb rubber processing factory PT. Sumber Djantin Pontianak. Research methods used to assess corporate entrepreneurship developed by Covin & Slevin models with multiple linear regression analysis method. Results of multiple linear regression analysis showed that the Corporate Entrepreneurship (X) positive and significant impact on Export Performance Company (Y) on crumb rubber processing factory PT. Sumber Djantin Pontianak, the regression equation: Export Performance = -5.421 + 0.868 Innovation + 1.158 Proactive + 0.395 willingness take Risks. Recommended for future research include other relevant variables impact on the success of the company Export Performance crumb rubber processing plant. And expand the use of new theories, so that research results can be generalized. Keywords: corporate entrepreneurship, export performance, and crumb rubber factory